PENGARUH PEMBELAJARAN BEMUATAN STEAM TERHADAP KEMAMPUAN BERPIKIR KRITIS ANAK USIA 5-6 TAHUN DI TK RAODHATUL JANNAH KABUPATEN TAKALAR - Rezki Ananda Yunita; Syamsuardi; Sri Rika Amriani; Tri Sugiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the effect of STEAM-based learning on the critical thinking abilities of children aged 5-6 years at Raodhatul Jannah Kindergarten, Takalar Regency. The research approach used is a quantitative approach with a Quasi Experimental Design research type. The population in this study were 20 group B children aged 5-6 years at Raodhatul Jannah Kindergarten, Takalar Regency. Sampling in this research was purposive sampling. The sample in this study was 16 group B children aged 5-6 years with 8 children as the experimental group and 8 children as the control group. The data collection technique used are tests, observation and documentation. The data collection procedures are planning, giving pre-test, giving treatment, giving post-test, and analyzing the results The data analysis technique used is descriptive statistical analysis and non-parametric statistical analysis using the Wilcoxon Sign Rank Test. Based on the research results, it can be concluded that the critical thinking abilities of children who were given STEAM learning treatment in the experimental group were better than those in the control group. The results of data analysis obtained an average increase in the experimental group of 19.88, while in the control group it was 11.50. The test results show sig. (2-tailed) 0.012 < 0.05 then H₀ is rejected and H₁ is accepted. So it can be concluded that learning with STEAM content has a significant influence on the critical thinking abilities of children aged 5-6 years at Raodtaul Jannnah Kindergarten, Takalar Regency.